PENGARUH INTEGRITAS, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA ANGGOTA DPRD YANG DIMEDIASI MOTIVASI KERJA (Studi pada DPRD Kalimantan Timur) - Khairul, Khairul; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to determine the influence of integrity, organizational culture and leadership style on the performance of DPRD members which is mediated by work motivation. The research sites were in 3 different locations, namely North Penajam Paser Regency DPRD, Paser Regency DPRD, Balikpapan City DPRD with a population of 89 DPRD members. Determining the number of samples used the Slovin formula, namely 73 people. The sampling technique used is probability sampling with the technique taken, namely proportionate stratified random sampling. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 4 software. The research results show that better integrity can encourage increased performance. Better integrity can encourage increased work motivation. Even though the organizational culture is getting stronger, it is not able to encourage increased performance. Even though the organizational culture is getting stronger, it is not able to encourage increased work motivation. A higher leadership style can encourage increased performance. A higher leadership style can encourage increased work motivation. Higher work motivation can encourage increased performance. Work motivation is able to play a role in mediating some of the indirect effects of integrity on performance. Work motivation is unable to play a role in mediating the indirect influence of organizational culture on performance. Work motivation is able to play a role in mediating some of the indirect effects of leadership style on performance.